Cost-effectiveness evaluation of escitalopram in major depressive disorder in Italy - Mencacci C; Di Sciascio G; Katz P; Ripellino C (Dove Medical Press, 2013)
Claudio Mencacci,1 Guido Di Sciascio,2 Pablo Katz,3 Claudio Ripellino31Ospedale Fatebenefratelli, Milan, Italy; 2Azienda Ospedaliera Universitaria Consorziale Policlinico di Bari, Bari, Italy; 3CSD Medical Research Srl, Milan, ItalyBackground: Depression has a lifetime prevalence of 10%–25% among women and 5%–12% among men. Selective serotonin reuptake inhibitors (SSRIs) are the most used and the most cost-effective treatment for long-term major depressive disorder. Since the introduction of generic SSRIs, the costs of branded drugs have been questioned. The objective of this study was to assess the cost-effectiveness (€ per quality-adjusted life year [QALY]) of escitalopram (which is still covered by a patent) compared with paroxetine, sertraline, and citalopram, the patents for which have expired.Methods: A decision analytic model was adapted from the Swedish Dental and Pharmaceutical Benefits agency model to reflect current clinical practice in the treatment of depression in Italy in collaboration with an expert panel of Italian psychiatrists and health economists. The population comprised patients with a first diagnosis of major depressive disorder and receiving for the first time one of the following SSRIs: escitalopram, sertraline, paroxetine, and citalopram. The time frame used was 12 months. Efficacy and utility data for the original model were validated by our expert panel. Local data were considered for resource utilization and for treatment costs based on the Lombardy region health service perspective. Several scenario simulations, one-way sensitivity analyses, and Monte Carlo simulations were performed to test the robustness of the model.Results: The base case scenario showed that escitalopram had an incremental cost-effectiveness ratio (ICER) of €4395 and €1080 per QALY compared with sertraline and paroxetine, respectively. Escitalopram was dominant over citalopram, which was confirmed by most one-way sensitivity analyses. The escitalopram strategy gained 0.011 QALYs more than citalopram, 0.008 more than paroxetine, and around 0.007 more than sertraline. Monte Carlo simulations indicated that ICER values for escitalopram were centered around €1100 and €4400 per QALY compared with paroxetine and sertraline, respectively. Although there is no official cost-effectiveness threshold in Italy, the value of €25,000 per QALY could be acceptable. All ICER values retrieved in all analyses were lower than this threshold.Conclusion: The findings from this cost-effectiveness analysis indicate that escitalopram could be accepted as a cost-effective strategy for the Lombardy region health service compared with the other SSRIs studied. The present assessment is based on ICER values resulting from this analysis, which are lower than the thresholds proposed by health care authorities in other European Union countries. These benefits are driven by the effectiveness of escitalopram, which result in an improved health-related quality of life, a higher probability of sustained remission, and better utilization of health care resources. The study results are robust and in line with other pharmacoeconomic analyses comparing escitalopram with other SSRIs.Keywords: CEA, depression, escitalopram, Lombardy, ICER, SSRI